2022
DOI: 10.3390/vaccines10030432
|View full text |Cite
|
Sign up to set email alerts
|

Risk Stratification of SARS-CoV-2 Breakthrough Infections Based on an Outbreak at a Student Festive Event

Abstract: In early 2022, the Coronavirus disease 2019 (COVID-19) remains a global challenge. COVID-19 is caused by an increasing number of variants of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Here, we report an outbreak of SARS-CoV-2 breakthrough infections related to a student festive event with 100 mostly vaccinated guests, which took place in Northern Bavaria, Germany, in October 2021. The data were obtained by retrospective guest interviews. In total, 95 students participated in the study, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…This may not be the case in a student festive event in Germany where a study reported that increased time spent, conversation with an index person, shared drinks and person-to-person direct contact at the event contributed to increased infection despite having been fully vaccinated. 16 The increase in number of breakthrough cases observed in the months of August to October 2021 coincided with the Philippines' uphill trend of cases as seen in Figure 1 due to the Delta variant surge. 17 A similar trend in the increase in cases was observed in a study done among fully vaccinated and unvaccinated university athletes belonging to the U.S.based National Collegiate Athletic Association in August to September 2021 which coincided with the start of school semester and possibly due to the higher transmissibility and breakthrough infections caused by the Delta variant.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This may not be the case in a student festive event in Germany where a study reported that increased time spent, conversation with an index person, shared drinks and person-to-person direct contact at the event contributed to increased infection despite having been fully vaccinated. 16 The increase in number of breakthrough cases observed in the months of August to October 2021 coincided with the Philippines' uphill trend of cases as seen in Figure 1 due to the Delta variant surge. 17 A similar trend in the increase in cases was observed in a study done among fully vaccinated and unvaccinated university athletes belonging to the U.S.based National Collegiate Athletic Association in August to September 2021 which coincided with the start of school semester and possibly due to the higher transmissibility and breakthrough infections caused by the Delta variant.…”
Section: Discussionmentioning
confidence: 72%
“…This may not be the case in a student festive event in Germany where a study reported that increased time spent, conversation with an index person, shared drinks and person-to-person direct contact at the event contributed to increased infection despite having been fully vaccinated. 16 …”
Section: Discussionmentioning
confidence: 99%